Radial migration in numerical simulations of Milky Way-sized galaxies - Grand, Robert J. J.; Kawata, Daisuke (Astronomische Nachrichten, 2016)
We show that in N-body simulations of isolated spiral discs, spiral arms appear to transient, recurring features that co-rotate with the stellar disc stars at all radii. As a consequence, stars around the spiral arm continually feel a tangential force from the spiral and gain/lose angular momentum at all radii where spiral structure exists, without gaining significant amounts of random energy. We demonstrate that the ubiquitous radial migration in these simulations can be seen as outward (inward) systematic streaming motions along the trailing (leading) side of the spiral arms. We characterise these spiral induced peculiar motions and compare with those of the Milky Way obtained from APOGEE red clump data. We find that transient, co-rotating spiral arms are consistent with the data, in contrast with density wave-like spirals which are qualitatively inconsistent. In addition, we show that, in our simulations, radial migration does not change the radial metallicity gradient significantly, and broadens the metallicity distribution function at all radii.
Gesehen am 31.07.2020